Manajemen Badan Amil Zakat Nasional Sumatera Utara dalam Meningkatkan Kesejahteraan Sosial Mustahik - Salsabila, Azzura Zahra; Sampurna, Ahmad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study aims to determine the management of the Empowerment of the North Sumatra National Amil Zakat Agency in improving mustahik social welfare. This study uses a descriptive qualitative approach to observe the natural conditions of the North Sumatra National Amil Zakat Agency. The data source of this study refers to mustahik conditions through non-part participant observation and semi-structured interview results. This research data is also sourced from journal articles, and relevant literature. In analyzing research data, researchers refer to the concept of reduction, presentation, and drawing conclusions. Data validity techniques This study refers to triangulation. The results of this study indicate that the North Sumatra Baznas plays a central role in improving mustahik welfare with a focus on zakat. Through the identification of poverty, surveys, and collaboration with local stakeholders, Baznas compiled sharia -based programs such as North Sumatra Care and North Sumatra Makmur. They changed the paradigm of giving zakat from consumptive to productive, involving training skills, financial education, and business capital. With a holistic approach, Baznas ensured that zakat improved mustahik welfare, reflecting productive investment for sustainable social welfare.